SISTEM INFORMASI TEMPAT PENYEWAAN PLAYGROUND (SITEPLON) BERBASIS WEB - Rangga Eka Yacha; Ahmad Khairii; Puja Rizki Saputra (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2022)
Playground activities are a fun playground for children and active movement for children is usually mostly when children are playing, and it is very helpful if there is a playground for children, especially in the current era that development Technology that is increasingly advancing rapidly has a very influential impact on children in the areas of growth such as playing and learning which is evident at this time being more interested in playing gadgets compared to active movement outside and inside the room. Thus, the author's goal to create a web-based Playground Rental Information System is to help provide a solution for parents to educate their children not only to play and learn through gadgets, but to balance it with active movement through the playground as one of the means. In addition, it helps vendors where playground rentals get promotions and encourages similar sesame vendors to compete fairly with each other to improve quality services, which has a good effect on the playground rental market itself. This Web-Based Playground Rental Information System was built using a software development method, namely the waterfall method and besides that in data collection, the authors also conducted observations and literature studies to strengthen scientific data and questionnaires to find deficiencies in the system that had been running so far.The results of the analysis show that providing actual and reliable information data is needed to adapt to increasingly fast technological developments to facilitate the search for related information. As one of the adjustment efforts by providing information through a programming medium.